دور القيادة التحويلية في تنمية الإبداع الإداري دراسة ميدانية على المصارف التجارية السورية في محافظة حماة - عمار قصي; سراقبي غالية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى دراسة دور نمط القيادة التحويلية في تنمية الإبداع الإداري، وذلك من خلال التعرف على دور أبعاد القيادة التحويلية، في تنمية القدرات الإبداعية بالنسبة للكوادر الإدارية العاملة في المصارف التجارية (العامة والخاصة) في محافظة حماة. لتحقيق هذا الهدف، استخدم الباحثان المقاربة الاستنباطية لتنمية فروض البحث؛ والاستبانة كأداة رئيسة لجمع البيانات من العاملين في المستويات الإدارية (الوسطى-الدنيا) في المصارف محل البحث. توصلت الدراسة إلى وجود علاقة طردية ذات دلالة معنوية بين القيادة التحويلية بأبعادها (التأثير المثالي، والتحفيز الإلهامي، والاستثارة الفكرية، والاعتبارية الفردية) وبين تنمية القدرات الإبداعية للعاملين في المصارف محل الدراسة. وكان من أهم التوصيات أن تهتمّ المصارف محلّ الدراسة بشكل أكبر بتطبيق ممارسات وسلوكيات القيادة التحويلية. This research aimed to study the role of Transformational Leadership Style in Administrative Creativity on Syrian Commercial Banks in Hama. By identifying the role of transformational leadership dimensions in developing creative abilities for administrative cadres working in the banks under study. In order to achieve the goals of this study, the researchers used the deductive approach. The study used a comprehensive inventory method for workers at the administrative (middle-lower) levels, consisting of (123). The researcher used the questionnaire as a main tool to collect data. The study concluded that there is a significant correlation between transformational leadership in its dimensions (ideal effect, inspirational motivation, intellectual stimulation, individualized consideration) and the development of Administrative Creativity of the employees in the banks under study. One of the most important recommendations was to be more concerned with the application of transformational leadership practices and behaviors.